2022
DOI: 10.1088/1361-6579/ac98f0
|View full text |Cite
|
Sign up to set email alerts
|

Pulse oximetry SpO 2 signal for automated identification of sleep apnea: a review and future trends

Abstract: Sleep apnea (SA) is characterized by intermittent episodes of apnea or hypopnea—paused or reduced breathing, respectively—each lasting at least ten seconds that occur during sleep. SA has an estimated global prevalence of 200 million and is associated with medical co-morbidities, and sufferers are also more likely to sustain traffic- and work-related injury due to daytime somnolence. SA is amenable to treatment if detected early. Polysomnography (PSG) involving multi-channel signal acquisition is the reference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…62 Several devices are being tested to measure sleep-related physiology in the ambulatory setting to simplify diagnosis and to augment or potentially replace polysomnography in selected cases. 63 Emerging devices use electrocardiographic and phonocardiographic sensors, oxygen sensors that can detect desaturations, 64 photoplethysmography to detect abnormalities in pulse waveforms, and sound sensors to detect snoring, as well as electroencephalographic and electromyographic sensors. 62…”
Section: Spectrum Of Physiological and Pathophysiological Measures: W...mentioning
confidence: 99%
“…62 Several devices are being tested to measure sleep-related physiology in the ambulatory setting to simplify diagnosis and to augment or potentially replace polysomnography in selected cases. 63 Emerging devices use electrocardiographic and phonocardiographic sensors, oxygen sensors that can detect desaturations, 64 photoplethysmography to detect abnormalities in pulse waveforms, and sound sensors to detect snoring, as well as electroencephalographic and electromyographic sensors. 62…”
Section: Spectrum Of Physiological and Pathophysiological Measures: W...mentioning
confidence: 99%
“…Recent research has shown that DL can be used to detect sleep apnea using SpO2 only with an acceptable degree of accuracy [ 20 ]. For example, one study found that a DL model based on an ANN architecture was able to detect sleep apnea with an accuracy of 97.8% [ 21 ].…”
Section: Related Workmentioning
confidence: 99%
“…For example, one study found that a DL model based on an ANN architecture was able to detect sleep apnea with an accuracy of 97.8% [ 21 ]. Generally, four main types of DL networks were widely used to detect OSA from SpO2 [ 20 ]. Earlier, a deep vanilla neural network (DNN) was used to learn simple patterns [ 22 , 23 ].…”
Section: Related Workmentioning
confidence: 99%
“…metabolic waste that accumulates during awakeness [1], [2]. In addition, reorganization and promotion of long-term memory is also done by good sleep.…”
mentioning
confidence: 99%